2022
DOI: 10.3390/en15196940
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Real-Time Control Platforms Using a Matlab/Simulink Coder with Applications in the Control of DC/AC Switched Power Converters

Abstract: In the control of DC/AC switched power converters (SPC), one of the most important aspects to be considered is the selection of the real-time control platform. The real-time control platform must be able to meet the high performance efficiency and regulation requirements of the DC/AC SPC, as these typically operate at switching frequencies in the order of kHz to MHz. For this reason, the hardware characteristics of the ADC and PWM, and the processing capacity of the real-time control platform are of vital impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It consists of a power electronic circuit, which includes electronic switches such as IGBTs, MOSFETs, capacitors, magnetic components, and a digital controller. The control algorithm is implemented in the digital controller, which is responsible for controlling the operation of the power electronic circuit [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Power Electronic Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of a power electronic circuit, which includes electronic switches such as IGBTs, MOSFETs, capacitors, magnetic components, and a digital controller. The control algorithm is implemented in the digital controller, which is responsible for controlling the operation of the power electronic circuit [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Power Electronic Circuitmentioning
confidence: 99%
“…Consequently, the number of publications devoted to power electronics is enormous (e.g., [1][2][3][4][5][6][7][8][9][10]), and similarly, many publications describe problems of digital signal processing (e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]). Only a few publications describe digital signal processing in the context of power electronics [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, simulation techniques have been suggested for optimizing various aspects of thermal power plants. For instance, the MATLAB®/Simulink platform has been used for real-time control in various applications [15], [16,17]. Additionally, simulation has been employed for optimizing coal transportation [18,19], [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The power amplifiers switching frequency were tuned to 10 KHz utilizing symmetric spacevector modulation. Further information and research activities on the microgrid test bed may be found in [28]- [30]. the literature which were proposed by EPRI.…”
Section: Experimental Validationmentioning
confidence: 99%